The level of use of information and communication technology at vocational high school - Purnamawati Purnamawati; Anas Arfandi; Nurfaeda Nurfaeda (Jurnal Pendidikan Vokasi, 2019)
Learning in the 4.0 era uses the concept of 4C (Communication, Collaboration, Critical Thinking, and Problem Solving, Creativity, and Innovation). This concept is linear to the use of information and communication technology (ICT). Technology literacy is involved in all subjects of learning. This phenomenon triggers the teachers, the students, and the school environment to play an active role so that technological progress has meaningfulness in increasing student competence. This study aims to: (1) describe the level of the use of ICT use, (2) determine the factors that influence the use of ICT, and (3) describe the ability of teachers to use ICT in the learning process. This research is a mixed-method with a sequential explanatory strategy. The data collected use questionnaires, interviews, observations, and documentation. The results obtained: (1) the level of ICT utilization in the learning process is at level 4, which means Managed and Measurable. (2) the factors that influence the use of ICT in the learning process in Makassar City Vocational High School based on the Resiliency Maturity Assessment Framework screen components namely data application factors, and (3) the ability teachers in utilizing ICTs in the learning process at Vocational High School in Makassar City meet the criteria very well.